Present Status of Monitoring Earthquakes in Kurdistan, Iraq - Khudhur, Fadhil I.; Ali, Bakir S.; Tawfiq, Aras M.; Ghalib, Hafidh A. A.; I.Aleqabi, Ghassan (Sulaimani Journal for Pure and Applied Sciences, 2016)
Kurdistan, Iraq, is located at the leading northeastern edge of the Arabian plate. Its tectonic framework is a manifestation of the northeast translational and counterclockwise rotational motion of the plate and its collision with the Iranian and Turkish plateaus. Historically, this dynamic setting has subjected the region to frequent seismic activity. Starting in 2005 Kurdistan embarked on collaborative projects to establish an advanced seismographic network that covers the region. The goal is to collect an unprecedented wealth of high quality data that can be effectively used to understand the seismotectonic framework and eventually the seismic risk throughout the region. In 2006 the North Iraq Seismographic Network (NISN) was deployed. It consists of ten three-component broadband stations equipped with STS-2 seismometers, 24 bits Q330 digitizers and 20GB Baler storage devices. In 2008, the five-element KSIRS array was added to further improve the network’s local and regional monitoring capabilities. KSIRS is equipped with STS-2 seismometers, 26 bits Q330HR digitizers, 16GB Marmot data loggers, and radio and satellite communication systems. The data are analyzed using the Antelope software system installed at the centers in Sulaimaniyah and Erbil. Since inception some of the NISN stations have been relocated. Plans are underway to build permanent underground vaults and equip all the stations with telemetry. So far this seismographic network has outperformed the international community’s reporting of the regional seismicity by 8:1. Participation in the virtual Middle East Seismographic Network (vMESN) has also greatly enhanced the NISN network performance.
Keywords: NISNKSIRSKurdistanIraqEarthquakesSeismic NetworkSeismic Stations